Testing precision and accuracy of weak value measurements in an IBM quantum system - (:unkn) unknown (AIP Publishing, 2024)
Historically, weak values have been associated with weak measurements performed on quantum systems. Over the past two decades, a series of works have shown that weak values can be determined via measurements of arbitrary strength. One such proposal by De...
Keywords: Computación cuántica; Mediciones débiles